Análise da severidade dos acidentes com motocicletas utilizando modelos probit e logit ordenados - Carlos Henrique Loiola Coutinho (2015)
: The Brazilian roadway traffic environmental has experienced a disproportionate development in the use of motorcycles over the last 15 years. The same trend has been observed for the number of traffic accidents in the category in partby their relative vulnerability. The objective of this study is to identify factors that influence the severity of motorcycleaccidents in urban streets of Fortaleza with the use of ordered probit and logit models. Ordered categorical models using asample of 3,232 observations of traffic accidents from 2004 to 2011 were developed. The resulting severity of traffic accidents was classified into four categories. The results of the model calibration indicated that riders who use helmets andtraveled during the day have a lower risk of suffering severe injuries. Otherwise, older riders and those involved in an accidenton the weekend had a higher risk of suffering more severe injuries.